Social policies and change in education-related disparities in mortality in Japan, 2000-2010 - Megumi Kasajima; Hideki Hashimoto (Elsevier, 2020)
Persistent socioeconomic disparity in mortality is a widely observed phenomenon despite improvements in the economic standard of living and the prevailing universal healthcare coverage policy. In this study, we selected Japan as a case in which public universal coverage has maintained horizontal equity in healthcare access while demographic and economic challenges have affected the life chances of vulnerable subpopulations over the past decade. We assessed the changing trends in the education-related disparity in mortality over a decade across demographic subpopulations for different causes of death, with the goal of generating social policy lessons to contribute to closing the mortality gap. Using a deterministic data merge between nationwide census and death records, we estimated age- and sex-specific mortality rates for 14 causes and their education-related gradients with absolute and relative indices of inequality in 2000 and 2010 via Poisson regression. Estimation parameters were standardized to the age structure of the sub-population of high school graduates in 2000 as the reference. The results demonstrated that the relative gaps in all-cause mortality persisted despite a decrease in the average mortality rate over the study period. The absolute gaps in mortality increased for preventable causes of death associated with lifestyle behavior choices. The average mortality worsened among socioeconomically vulnerable populations such as youth and women, who were left behind in the existing social/economic policy. External causes of death such as suicide and traffic accidents showed decreasing absolute gaps in a subpopulation targeted by universal social and labor policy measures. These change patterns indicate that, compared with a high-risk approach, a universal policy approach to dealing with societal and fundamental causes of health inequality seems more effective in reducing the education-related mortality gap in both absolute and relative terms.